21 Phase encoding direction and position effects on ADC in diffusion MRI: An AFIM multisite comparison study. (December 2018) - Fedeli, L; Belli, G.; Ciccarone, A.; Coniglio, A.; Esposito, M.; Giannelli, M.; Gobbi, G.; Gori, C.; Mazzoni, L.N.; Nocetti, L.; Sghedoni, R.; Tarducci, R.; et al.
Abstract : Purpose: The dependence of ADC (measured in isotropic phantom) on position and ADC phase encoding may be used to test MRI scanner performances and may play relevant effect on quantitative data accuracy in clinical imaging. Quantitative results of AIFM multicentre intercomparison are reported. Methods: Twenty-six MR scanners (20/6 1.5 T/3.0 T magnetic field strength) were enrolled in this study. Custom spherical water phantom (14 cm diameter) specifically designed for DWI QA was provided to all participants. ADC value was certified as in[1] . Phantom was placed at isocentre of scanner. Using three DWI sequences (b-value varying form 0 s/mm 2 to 1000 s/mm 2 ), differing for the gradient diffusion direction (Gdd), 5 mm thick axial slices were acquired (5 mm gap). Acquisition was repeated exchanging frequency and phase encoding direction. ADC maps were generated for each Gdd. Seven 2 × 2 cm 2 ROIs were considered: one at isocentre and six in periphery (left, right, superior, inferior, head and feet). For each acquisition, maximum relative difference between periphery and central ROIs ADC was calculated ( δ ADC % x, y, z ) . Maximum δ ADC % x, y, z with respect to three acquisitions ( δ M%) was also considered. As for phase/frequency encoding direction dependences, ADC x, y, z differences on central ROI were measured. Results: Differences Absolute value of δ M is below 5% for 19 scanners, 18 scanners show δ M > 0. Spatial direction of maximal variation is "x" in 23 scanners, "y" in the other. Gdd associated to δ M is x/y/z for 9/12/5 scanners. Differences between −2% and +1% have been observed with respect to phase encoding direction. Conclusions: A simple protocol for quantitative evaluation of ADC spatial and phase encoding dependence has been proposed. Difference in ADC between isocentre and periphery should be consider in precision ADC measurements.